Consumer Comprehension of the Nutrition Facts Label: A Comparison of the Original and Updated Labels. Issue 5 (June 2021) - Kim, Elizabeth Jiyoon; Ellison, Brenna; Prescott, Melissa Pflugh; Nayga, Rodolfo M.
Purpose: Compare consumers' overall label comprehension of the original Nutrition Facts (NF) label with the updated label. Design: Online survey conducted in 2019. Participants randomly assigned to original label, updated-single column, or updated-dual column labeling condition and asked to complete a series of label comprehension questions. Setting: Online survey; participants recruited through Prolific. Sample: N = 992 U.S. adults. Sample similar to U.S. population in terms of sex (49.2% female), race (73.3% White/Caucasian), and household size (mean = 2.7 members). However, sample was younger (median age: 29.0), more educated (98.8% high school graduate or higher), and exhibited a lower rate of obesity (22.6% obese) than the U.S. population. Measures: Dependent variables: objective (% correct) NF label comprehension. Independent variables: label condition, nutrition knowledge, and socio-demographic variables. Analysis: Regression analysis assessed relationships between label condition and label comprehension. Significance level of 5% used for analyses. Results: Average score for objective comprehension was 81.4%. The updates did not significantly improve label comprehension. Participants in the updated NF label conditions had trouble answering questions related to total and added sugars. Conclusions: Results suggest consumers may struggle to correctly utilize information on the updated NF label, specifically total and added sugars. Consumers may benefit from educational opportunities on using the new label.